Internet Gaming Disorder, Risky Online Behaviour, and Mental Health in Hong Kong Adolescents: The Beneficial Role of Psychological Resilience - Tsui, Yvonne Yin-yau; Cheng, Cecilia (Frontiers in Psychiatry, 2021)
In the present cyber age, Internet gaming disorder (IGD) and risky online behaviour are prevalent, and adolescents are especially vulnerable to such emergent problems. Few studies have explored the protective factors that mitigate harm caused by IGD and various common risky online behaviours. This study examined the prevalence of IGD and risky online behaviour, their hypothesised associations with depressive symptoms, and the beneficial role of psychological resilience as an underlying psychological mechanism. The participants included 1,099 Chinese junior secondary school students (33% boys, mean age = 13.5 years, age range = 10–17 years) who completed a battery of validated self-report questionnaires at their schools. The results revealed that 4% of the participants were at high risk of IGD and 6% were at an overall risk level of IGD. Depressive symptoms were positively associated with IGD and risky online behaviour, and psychological resilience mediated both of these associations. These results imply that clinicians and teachers should incorporate psychological resilience training into intervention approaches to mitigate IGD and risky online behaviour.